Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1103/physrevb.69.161306
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced oscillatory Hall effect in high-mobilityGaAs/Alx

Abstract: We examine the radiation induced modification of the Hall effect in high mobility GaAs/AlGaAs devices that exhibit vanishing resistance under microwave excitation. The modification in the Hall effect upon irradiation is characterized by (a) a small reduction in the slope of the Hall resistance curve with respect to the dark value, (b) a periodic reduction in the magnitude of the Hall resistance, Rxy, that correlates with an increase in the diagonal resistance, Rxx, and (c) a Hall resistance correction that dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
124
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(134 citation statements)
references
References 15 publications
(36 reference statements)
9
124
1
Order By: Relevance
“…. 7 The fits results, see Fig. 3, indicate that λ ≈ 0.26T , which corresponds to T f ≈ 260mK, is constant and insensitive to f , within experimental uncertainties.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…. 7 The fits results, see Fig. 3, indicate that λ ≈ 0.26T , which corresponds to T f ≈ 260mK, is constant and insensitive to f , within experimental uncertainties.…”
Section: Methodsmentioning
confidence: 91%
“…In ref. 7 , λ was shown to be insensitive to f over the band 30 < f < 120GHz. Thus, these results suggest similar behavior over the band examined in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the DC biases on the ZRS has been studied in paper [20]. It was found that the microwave radiation makes the response to the dc electric field to be more linear.…”
mentioning
confidence: 99%
“…From the experimental standpoint, remarkable contributions are being published in a continuous basis. Among them we can highlight activated temperature dependence in the magnetoresisitivity (ρ xx ) response 3,4,5 , quenching of ρ xx response at high microwave (MW) intensities 2,6 , absolute negative conductivity (ANC) and breakdown of ZRS 2,5,6,7 , suppression of MIRO and ZRS by in-plane magnetic field 8,9 and the evidence that MIRO and ZRS are notably immune to the sense of circular polarization of MW radiation 10 . Very recently, an experimental achievement has joined the group of new contributions.…”
Section: Pacs Numbersmentioning
confidence: 99%